Patterns and Differences of Acetabular Dome Wear of Normal and Operated Hip Joints between the Unipolar and Bipolar Prostheses in the Femoral Neck Fracture Surgery - Songviroon, MD, Surat; Leownorasate, MD , Manoon (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To describe the patterns and differences of wear at acetabular dome wall of the normal and the operated hip joints between the unipolar and bipolar prostheses in the femoral neck fracture surgery. Patients and Methods: The medical records and radiographic imagings of femoral neck fracture patients who were treated with the unipolar or bipolar prostheses at Maharat Nakhon Ratchasima Hospital since July 2010 to September 2015 were reviewed. The acetabular dome wall thickness (ADWT) was measured on true antero-posterior view of both sides of hip joints at the 1st day and every 6 months after surgery. The measurements were designed with various methods for minimizing the deviation and error and detail would be shown in text below. The patterns and differences of wear at acetabular dome wall between operated side and normal side were described. The patient demographic data and the wear at acetabular dome wall were compared between the unipolar and bipolar prostheses groups. A p-value of less than 0.05 was considered statistically significant. Results: All 152 patients were classified into 83 with unipolar and 69 with bipolar prostheses groups. The wear pattern at acetabular dome wall on the normal side was not significantly different in both groups. After sex, ADWT on the operated side at 1 day after surgery and age groups adjusted, the wear differences between two groups were statistically significant at 6, 12, 24, and 30 months after surgery with mean differences of 0.307, 0.609, 0.825, and 2.460, respectively. Conclusion: The wear patterns at acetabular dome wall in femoral neck fracture surgery were different between the unipolar and bipolar prostheses. They were statistically significant only at 6, 12, 24, 30 months after surgery.